STUDI ALTERNATIF PENGGUNAAN SERAT KELAPA (COCOFIBER) UNTUK KEKEDAPAN SAMBUNGAN KULIT PADA KAPAL KAYU TRADISIONAL DENGAN PENGUJIAN HIDROSTATIS - Manik, Parlindungan; Kiryanto, Kiryanto (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2008)
This study explains about the use of coco fiber as an alternative material in ship impermeability process. At impermeability process of traditional wooden ship is applied by bark gelam or by twisted jute fiber as component of caulk for impermeability of junction bark of ship, where at this caulker still leak on bark of wooden ship.Impermeability technology by using bark gelam or by twisted jute fiber which was caulked at junction bark of ship. There is still leak on bark of ship, so this research was applied lay-up coco-fiber with resin as alternative material to overcome leak problem bark of wooden ship.The methodological study was started with make specimen test, after that the putty process with lay up coco fiber with resin and catalyst, and than doing hydrostatic testing. Finally, we analyze the result of research can be used in putty of wooden ship.The result of research, it was concluded that in general pressure maximum each bevel specimen which could endure burden on the bark of ship i.e. : for board joint design 150 is 99,67 lbf/in2 , for board joint design 300 is 91,67 lbf/in2 and for board joint design 450 is 66 lbf/in2. With the result in general pressure maximum above, the bark can receive burden at draft (T) i.e. : for bevel 150 is 68,38 meter (m), for bevel 300 is 62,86 meter (m), and for bevel 450 is 45,16 meter (m).The Putty technology used variety bevel specimen i.e. bevel 150, 300 end 450 could be applicated for impermeability of junction bark of traditioanl vessel